2015
DOI: 10.1371/journal.pone.0133452
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Development of Drug Resistance Mutations in HIV-1 Infected Children Failing Protease Inhibitor-Based Antiretroviral Therapy in South Africa

Abstract: ObjectiveLimited data are available from the developing world on antiretroviral drug resistance in HIV-1 infected children failing protease inhibitor-based antiretroviral therapy, especially in the context of a high tuberculosis burden. We describe the proportion of children with drug resistance mutations after failed protease inhibitor-based antiretroviral therapy as well as associated factors.MethodsData from children initiated on protease inhibitor-based antiretroviral therapy with subsequent virological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…Concomitant Tuberculosis treatment while on second-line ART was higher among cases (67%) and signi cantly associated with second-line failure with PI mutations (p=<0.001). Our ndings are in line with a study conducted by Rossouw et al 2015, which found that children on Tuberculosis treatment while on second-line ART were more likely to fail on second-line therapy with PI mutations [21]. This is attributable to factors such as higher pill burden [32,33], HIV/TB coinfection being associated with advanced HIV/AIDS [34], and the fact that Rifabutin is not readily available in the resource-limited settings as a replacement for Rifampicin which is known to reduce the pharmacookinetic levels of PIs and consequently their their e cacy [35,36].…”
Section: Hiv/tb Coinfection and Second-line Art Failure With Pi Mutatsupporting
confidence: 93%
See 1 more Smart Citation
“…Concomitant Tuberculosis treatment while on second-line ART was higher among cases (67%) and signi cantly associated with second-line failure with PI mutations (p=<0.001). Our ndings are in line with a study conducted by Rossouw et al 2015, which found that children on Tuberculosis treatment while on second-line ART were more likely to fail on second-line therapy with PI mutations [21]. This is attributable to factors such as higher pill burden [32,33], HIV/TB coinfection being associated with advanced HIV/AIDS [34], and the fact that Rifabutin is not readily available in the resource-limited settings as a replacement for Rifampicin which is known to reduce the pharmacookinetic levels of PIs and consequently their their e cacy [35,36].…”
Section: Hiv/tb Coinfection and Second-line Art Failure With Pi Mutatsupporting
confidence: 93%
“…For example, in a small cohort of 44 patients, Chimbetete et al 2018 found age as the only factor associated with failure on second-line ART with PI mutations whereby patients above 24 years of age were at a higher risk of failing with major PI mutations [20]. Another study among children less than three years of age highlighted; timing of Tuberculosis treatment while on second-line ART and protease inhibitor dosing strategy [21].…”
Section: Failure On Second-line Antiretroviral Therapymentioning
confidence: 99%
“…HIV-1 drug resistance occurs rapidly among infants due to the infants' conditions, such as a higher HIV-1 viral load than that in adults, poor tolerance of ART medication, complex adherence issues, and previous exposure to ART in order to prevent MTCT [42,43,44]. In infants with co-infections such as tuberculosis, treatments may increase adverse events, including drug toxicity and the risk of significant inter-drug interactions.…”
Section: Appearance Of Drug Resistance-associated Mutations In Rmentioning
confidence: 99%
“…It is important to understand the interplay of factors associated with HIV drug resistance, especially in low to middle-income countries (LMICs) where there is limited access to viral load testing [17]. In this study we used data collected from the AIDS Prevention Initiative in Nigeria (APIN) program, a comprehensive HIV care and treatment program in the country, to evaluate sociodemographic, socioeconomic and other factors that could be associated or predict ADR in Nigeria.…”
Section: Introductionmentioning
confidence: 99%